Pengaruh Perubahan Arus Kas Operasi terhadap Likuiditas dan Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI - Wardiningsih, Reny (YASIN, 2021)
This study aims to determine the effect of operating cash flow on liquidity and profitability in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study were manufacturing companies in 2015-2019, which amounted to 155 companies. The sampling technique used was purposive sampling technique so that a sample of 28 companies was obtained. The data analysis technique used simple linear regression analysis. Based on the results of the t-test with SPSS IBM 20, it was found that operating cash flow had no effect on liquidity as proxied by the Current Ratio (CR) because the t-count value was smaller than t-table (0.427 < 1.665) and significant value (0.670 > 0.05), and operating cash flow has an effect on profitability which is proxied by Return On Assets (ROA) because the value of t-count is greater than t-table (2.646 > 1.665) and significant value (0.010 < 0,05).